Ultrasound-measured umbilical cord area predictor of fetal macrosomia - Lacunza Paredes, Rommel Omar (2014)
Objective: To demonstrate that the umbilical cord area measured by ultrasound is a predictor of fetal macrosomia in term singleton fetuses. Design: Descriptive, observational, cross sectional study. Setting: Hospital Nacional Daniel Alcides Carrion, Callao, Peru. Participants: Pregnant women at term. Interventions: Ultrasound anthropometric parameters, Hadlock formula, Cromi formula and cross-sectional area in a free loop of the umbilical cord were determined in 181 pregnant women at term with single fetus. Logistic regression was used to determine predictors of fetal macrosomia. Main outcome measures: Prediction of fetal macrosomia. Results: The prevalence of fetal macrosomia detected by ultrasound was 41.9%. The proportion of cases of umbilical cord area above the 95th percentile was significantly higher in cases of infants with macrosomia (85% versus 34.2%). The multiple regression model demonstrated the independent contribution of the umbilical cord area above the 95th percentile as a predictor of macrosomia with sensitivity 86.6%, specificity 65.7%, positive predictive value 64.35% and negative predictive value 86%. The ROC curve showed the area under the curve of the umbilical cord area above the 95 percentile was higher (0.75) than the ultrasound fetal weight by Hadlock formula (0.74). Conclusions: The umbilical cord area above the 95th percentile for gestational age is a good predictor of fetal macrosomia in term singleton fetuses. Keywords: Fetal macrosomia, umbilical cord, ultrasonography.